Serum uric acid: A risk factor for right ventricular dysfunction and prognosis in heart failure with preserved ejection fraction - Deng, Xiang-liang; Yi, Han-wen; Xiao, Jin; Zhang, Xiao-fang; Zhao, Jin; Sun, Min; Wen, Xue-song; Liu, Zhi-qiang; Gao, Lei; Li, Zi-yang; Ge, Ping; Yu, Qi; et al. (Frontiers in Endocrinology, 2023)
Background: Hyperuricemia and right ventricular dysfunction (RVD) are both widespread in heart failure with preserved ejection fraction (HFpEF) patients. RVD is associated with a poor prognosis in HFpEF. The correlation between serum uric acid (UA) levels and right ventricular function is unclear. The prognostic performance of UA in patients with HFpEF needs further validation. Methods and Results: A total of 210 patients with HFpEF were included in the study and divided into two groups according to UA level: normal UA group (≤7 mg/dL) and high UA group (>7 mg/dL). The variables examined included clinical characteristics, echocardiography, and serum biochemical parameters. Right ventricular function was assessed by tricuspid annular plane systolic excursion (TAPSE) and tricuspid annular peak systolic velocity (TAPSV). Baseline characteristics were compared between two groups, and the correlation between baseline UA and RVD was assessed using multifactorial binary logistic regression. Kaplan-Meier curves were used to describe all-cause mortality and hospitalization for heart failure. Results showed that right ventricular function parameters were worse in high UA group. After adjusting for UA, left ventricular posterior wall thickness (LVPWT), N-terminal B-type natriuretic peptide (NT-proBNP), atrial fibrillation (AF) and low-density lipoprotein cholesterol (LDL-C), UA (odds ratio =2.028, p<0.001) was independently associated with RVD, and UA >7 mg/dL (HR=2.98, p<0.001) was associated with heart failure readmission in patients with HFpEF. Conclusion: Elevated serum UA is closely associated with RVD and significantly associated with heart failure readmission rate in patients with HFpEF.